The Relationship Between Religiosity and Performance on Competition Anxiety Among Male Basketball Athletes of the POPDA Team in Brebes Regency - Nandana Adiyatma Kusuma; Dwi Gansar Santi Wijayanti (Universitas Negeri Semarang, 2025)
Competition anxiety in basketball athletes can be influenced by poor performance. Good performance can boost self-confidence, thereby reducing anxiety before a match. Religiosity is another factor that may alleviate competition anxiety. This study aims to examine the relationship between religiosity and performance on Competition anxiety among male basketball athletes of the POPDA team in Brebes Regency. The research employs a correlational quantitative approach with total sampling technique. Data were collected using questionnaires for religiosity and anxiety, as well as performance tests (physical and technical skills). The results indicate: A strong correlation between religiosity and anxiety (r = 0.678; p = 0.05). A strong correlation between performance and anxiety (r = 0.788; p = 0.00). Simultaneously, religiosity and performance significantly influence anxiety (F = 124.637 > F-table = 3.81; p = 0.00). Partial t-tests further confirm that both religiosity (t = 3.841) and performance (t = 2.595) positively and significantly affect anxiety. Overall, 75% of anxiety variability is influenced by religiosity and performance. Showed that religiosity and athlete performance had a significant role in reducing male basketball athletes’ match anxiety. Higher levels of religiosity and better performance were strongly associated with lower levels of anxiety prior to competition. Together, these two factors accounted for 75% of the variability in athletes’ anxiety levels, highlighting their substantial combined impact.